Partially Mobile Adsorption of a Single Gas on a Microporous Adsorbent - J.K. Garbacz; A. Dabrowski (Adsorption Science & Technology, 1995)
The model of partially mobile adsorption on microporous solids has been formulated for the cases of energetically homo- and heterogeneous adsorbents. Ethane and xenon adsorption isotherms on various forms of zeolite have been described by relationships derived from the proposed adsorption model.